The influence of the e-performance appraisal system, education and competence on employee performance through spiritual motivation in the regional office of the Ministry of Religion Riau Islands Province - Hairul, Hairul; Wibisono, Chablullah; Catrayasa, I Wayan (Goodwood Publishing, 2024)
Purpose: This study aimed to analyze the influence of the e-performance assessment system, education, and competence on employee performance, as well as the mediating role of spiritual motivation at the Regional Office of the Ministry of Religion of the Riau Islands Province. Research Methodology: The study involved 104 respondents comprising State Civil Apparatus (PNS and PPPK). Data were collected through surveys and analyzed using the Structural Equation Modeling (SEM) approach with SmartPLS 3.0. Results: The findings show that the e-performance assessment system significantly improves employee performance, whereas education and competence do not. Spiritual motivation has a strong positive impact on performance. Furthermore, the e-performance system, education, and competence significantly influenced spiritual motivation. Mediation analysis indicates that spiritual motivation mediates the relationship between the e-performance system and competence with employee performance, while the mediation of education is positive but insignificant. Conclusions: The e-performance system and competence are key drivers of employee performance when reinforced by spiritual motivation, underscoring the importance of psychological and spiritual factors in public-sector performance. Limitations: This study was limited to one regional office and a relatively small sample size, which may affect the generalizability of the findings. Contribution: This research enriches the public sector performance management literature by integrating spiritual motivation as a mediating factor. This study provides insights for policymakers to design e-performance systems that not only strengthen competence but also foster spirituality, thereby enhancing sustainable employee performance.